Aspectos neuropsicológicos da linguagem em adolescentes em conflito com a lei - Morais, Everton Adriano de (2017)
The present study aims to investigate and evaluate the neuropsychological language in adolescents in conflict with the law. FAS (Verbal fluency), Wechsler Abbreviated Scale of Intelligence Vocabulary Subtest (WASI) and Cloze's word reader comprehension test. 25 adolescents institutionalized in conflict with the law of the city of Ponta Grossa / PR and 17 school adolescents without conflict with a law of the city of Curitiba / PR, both male groups, were selected for convenience. After the application of the tests were compared and correlated with the data obtained, those referring to the adolescents in conflict with the law, hereafter offenders and adolescents without conflict with a law, henceforth non-offenders, were identified as statistically significant in the FAS test (U = 122,00, p = 0.020) and no vocabulary subtest (U = 108.50, p = 0.008). We also compared adolescents in conflict with one bed, recurrent and non-recurrent, but no significant differences were found between the two groups. Finally, a sample of infraction acts involving homicide or homicide crime was analyzed and it was possible to identify FAS (U = 35.50, p = 0.037). The results found corroborated the literature regarding the development of language, its neuropsychological principles and the infraction, supporting research for the forensic and neuropsychological area